2019
DOI: 10.1016/j.ajhg.2019.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Bi-allelic Variants in IQSEC1 Cause Intellectual Disability, Developmental Delay, and Short Stature

Abstract: We report two consanguineous families with probands that exhibit intellectual disability, developmental delay, short stature, aphasia, and hypotonia in which homozygous non-synonymous variants were identified in IQSEC1 (GenBank: NM_001134382.3). In a Pakistani family, the IQSEC1 segregating variant is c.1028C>T (p.Thr343Met), while in a Saudi Arabian family the variant is c.962G>A (p.Arg321Gln). IQSEC1-3 encode guanine nucleotide exchange factors for the small GTPase ARF6 and their loss affects a variety of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 94 publications
0
15
0
Order By: Relevance
“…Recessive, rare mutations in IQSEC1 are associated with intellectual developmental disorder with short stature and behavioral abnormalities (OMIM #618687). Ansar et al (2019) recently reported the first case of bi-allelic pathogenic variants in IQSEC1 . Functional studies suggested that the pathogenic IQSEC1 variants resulted in defects in axon guidance and dendritic projection processes.…”
Section: Discussionmentioning
confidence: 99%
“…Recessive, rare mutations in IQSEC1 are associated with intellectual developmental disorder with short stature and behavioral abnormalities (OMIM #618687). Ansar et al (2019) recently reported the first case of bi-allelic pathogenic variants in IQSEC1 . Functional studies suggested that the pathogenic IQSEC1 variants resulted in defects in axon guidance and dendritic projection processes.…”
Section: Discussionmentioning
confidence: 99%
“…LGR6 (luteinizing hormone receptor 6) is expressed in embryonic hair follicles, and acts as a marker in the most primitive epidermal stem cells [54]. A mutation in IQSEC1 can cause intellectual disability, developmental delay, and short stature [55]. KCNA5 (potassium voltage-gated channel subfamily A member 5) genes, associated with pulmonary arterial hypertension (PAH) [56], may affect the motion of the horse.…”
Section: Discussionmentioning
confidence: 99%
“…Targeted depletion of IQSEC1 after P21 resulted in smaller NMDA/AMPA current ratios at Schaffer collateral synapses (Elagabani et al., 2016) and the same change has been observed in Fmr1 KO mice (Aloisi et al., 2017). In addition, targeted depletion of IQSEC1 throughout development in projection neurons of the cortex resulted in an increased density of dendritic spines and in a higher fraction of spines with small heads (Ansar et al., 2019), similar to the morphological abnormalities of dendritic spines observed in FXS patients and in Fmr1 KO mice (Irwin et al., 2001, 2002). These results collectively support a developmental stage‐dependent loss of IQSEC1 and IQSEC2 recruitment in Fmr1 KO mice.…”
Section: Discussionmentioning
confidence: 81%
“…The density and morphology of spines in neuronal cultures were shown to depend on the dosage of Iqsec2 (Hinze et al., 2017). In addition, we recently found an increased frequency of immature spines upon targeted depletion of IQSEC1 in cortical projection neurons of mice (Ansar et al., 2019). Finally, variants in the X‐chromosomal human gene IQSEC2 (Kalscheuer et al., 2015; Shoubridge et al., 2010, 2019; Zerem et al., 2016) and biallelic variants in IQSEC1 (Ansar et al., 2019) and IQSEC3 (Monies et al., 2019) were identified in individuals and families with ID, developmental delay and in some cases with seizures, aggressive, and autistic behaviors.…”
Section: Introductionmentioning
confidence: 93%